(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study analyzes the tradition as a pillar of socio-cultural resilience in the era of globalization. The ruwatan ceremony functions as a form of local wisdom that reflects the community’s worldview, social values, and spiritual beliefs. In the midst of modernization and lifestyle changes, this tradition faces challenges to its continuity; however, it simultaneously demonstrates adaptability and the capacity to sustain cultural identity. This research employs a qualitative method with an ethnographic approach. Data were collected through field observations, in-depth interviews with community leaders, cultural practitioners, and local residents, as well as documentation of wayang golek ruwatan performances. Data were analyzed thematically to identify the cultural functions and resilience strategies embedded in the tradition. The findings reveal that the ruwatan wayang golek tradition serves as an instrument of socio-cultural resilience by fostering collective identity, intergenerational cultural transmission, and moral education. The performance conveys at least 18 core character values, and these values strengthen social cohesion and reinforce community solidarity amid global cultural influences. Furthermore, the adaptation of performance contexts and narratives enables the tradition to remain relevant in contemporary society.